Fiber prepared via swelling and thermal cross‐linking as reusable Fenton catalyst for methylene blue decolorization. Issue 8 (8th June 2018) - Lv, Yuanyuan; Xu, Naiku; Feng, Yan; Lu, Yuyao
Abstract: Swelling was first adopted to transform the close‐packed structure of as‐spun poly (acrylic acid‐co‐hydroxyethyl methacrylate) fiber prepared via wet spinning into loose and porous structure. This structure enabled the fiber to carry a large number of iron ions within a certain period of time. Thermal cross‐linking was subsequently conducted to prevent methylene blue solution leaching iron ions out from the fiber. The Fenton catalyst based on the combination of the fiber and iron ions prepared via swelling and thermal cross‐linking exhibited excellent reusability in decolorizing MB. The research results showed that more than 95% of MB could be decolorized from 10 ml of MB solution with the concentration of 20 mg/L in the presence of 2 μl of H2 O2 and about 5 mg of virgin catalyst, and even when the catalyst was used for the tenth time, MB decolorization efficiency still reached up to 88%. In addition, the difference of swelling processes also caused the result that the corresponding catalysts had different thermal properties.